Long-term survival after CCRT and HAIC followed by ALPPS for hepatocellular carcinoma with portal vein invasion: a case report - In-Jung Kim; Sung Hwan Yoo; Jung Il Lee; Kwan Sik Lee; Hyun Woong Lee; Jin Hong Lim (Journal of Liver Cancer, 2022)
There are various methods for treating advanced hepatocellular carcinoma with portal vein invasion, such as systemic chemotherapy, transarterial chemoembolization, transarterial radioembolization, and concurrent chemoradiotherapy. These methods have similar clinical efficacy but are designed with a palliative aim. Herein, we report a case that experienced complete remission through “associating liver partition and portal vein ligation for staged hepatectomy (ALPPS)” after concurrent chemoradiotherapy and hepatic artery infusion chemotherapy. In this patient, concurrent chemoradiotherapy and hepatic artery infusion chemotherapy induced substantial tumor shrinkage, and hypertrophy of the nontumor liver was sufficiently induced by portal vein ligation (stage 1 surgery) followed by curative resection (stage 2 surgery). Using this approach, long-term survival with no evidence of recurrence was achieved at 16 months. Therefore, the optimal use of ALPPS requires sufficient consideration in cases of significant hepatocellular carcinoma shrinkage for curative purposes.